Discrete-time multirate LQG control of a DC motor speed control system - Wang, Haipeng (2008)
This report describes the development of a new discrete-time multirate LQG (hereafter called MRLQG) controller. The project involves the design and simulation of a MRLQG controller for a DC Motor Speed Control System with the aim to improve tracking responses.